Physical therapy students’ perceptions of embedded medical librarians within evidence-based practice courses: a mixed-methods pilot study - Bolgla, Lori; Novak, Malorie; Smith, Lachelle (Journal of the Medical Library Association, 2025)
Objective: Previous work within academic medical centers has indicated the potential value of embedded medical librarian programs within health sciences professional degree programs. This study sought to determine the perceived benefit that an embedded medical librarian (EML) provided to an evidence-based practice (EBP) course within an entry-level physical therapy degree program. Methods: Learners completed an anonymous survey at the end of an EBP course about the impact of the EML on the course and their own EML utilization. Frequency and percentages were calculated for quantitative data; qualitative data were analyzed using an iterative process for code development. Results: Forty (98%) learners completed the survey. Seventy-five point six percent of learners utilized the EML 1-2 times per class session and 31.7% outside of class sessions. Learners overwhelmingly “agreed” (53.7%) or “strongly agreed” (39.0%) that they would consult the EML for literature searches required in future courses. Seventy point seven percent “strongly agreed” that the EML improved their ability to conduct a literature search. All learners either “agreed” (43.9%) or “strongly agreed” (56.1%) that the EML added value to the course. Ninety point two percent considered the EML as an integral part of the course. Themes from the qualitative analysis agreed that the EML added value to the course and facilitated skills that would be useful throughout the curriculum. Conclusion: Learners believe that having an EML improves their ability to conduct a literature search. Providing learners with EML access during their education experience facilitates development of this skill. Early and continued instruction throughout the entry-level DPT curriculum in informatics ensures program compliance with accreditation standards.